ANCESTRAL INTELLIGENCE AND ADAPTIVE SYSTEMS- BIOMIMICRY AS A BRIDGE FOR GLOBAL CONTINUITY IN JAIPUR CLOTHING EMBELLISHMENT TECHNIQUES - Gupta, Nagendra Kumar; Yadav, Sunita (ShodhKosh: Journal of Visual and Performing Arts, 2026)
While commonly viewed as a recent approach to innovation by mimicking biology in technological designs, biomimicry had been practiced by indigenous textile traditions prior to the establishment of such a field of science through material adaptability, cyclical modes of production, and patterning systems based on observations of ecology. The following research will focus on analysing Jaipur’s textile decoration traditions, including techniques like block printing, resist dyeing, embroidery, and motif creation inspired by flora and fauna, as embodied biomimetic design systems that evolved independently of any theory. Following the design of a convergent mixed method research strategy, the research uses ethnographic interviews with 26 artisans, sustainability perception questionnaires conducted among 128 artisans, morphological analysis of motifs, and Life Cycle Assessment modelling according to ISO 14040/44 standards. The analysis of collected data showed that the water consumption and waste intensity in traditional production were significantly lower than in machine-assisted techniques (p < 0.05). Waste intensity differences were found to vary between 27% and 62%. Morphology analysis also demonstrated the biomimetic characteristics of Jaipur’s floral motifs in terms of structure similarities to growth forms with radial symmetry and recursive scale patterning’s. Based on these results, the paper further proposes a model entitled the Three-Layered Adaptive Continuity Model where the concepts of Material Science (Body), Digital Biology (Mind) and Heritage Preservation (Soul) work together as inter-related components of a regenerative craft system. By shifting the understanding of traditional textile heritage into an adaptation of adaptive bio-cultural infrastructure, the study offers insights into sustainable practices in sustainability, regenerative design and biomimicry literature. Thus, the Jaipur case becomes a unique example of a sustainable transition approach, which combines the use of embodied knowledge with recycling of material elements.